Application of IAC Yokohama System For Reporting Breast Fine Needle Aspiration- A Retrospective Study - Sharma, Upender; Beniwal, Atul; Sharma, Sonam; Singh, Ajit; Kamra, Hemlata T (Annals of Pathology and Laboratory Medicine, 2021)
Background: Breast cancer is one of the most common cancers worldwide in females and is an important cause of mortality and morbidity. FNAC is a safe, reliable, sensitive, specific, time saving and cost effective procedure useful in the diagnosis of carcinoma breast. It helps the surgeon in planning the treatment, and thereby reducing the delay in treatment. The primary aim of this study is to find out the spectrum of breast lesions on fine needle aspiration cytology based on IAC Yokohama system in a tertiary care hospital of north central Haryana. Methods: This is a retrospective study carried out in a tertiary care hospital of north-central Haryana and included 417 patients of palpable breast lumps presented in the Department of Pathology for FNAC during January 2018 to December 2019. FNAC was done under all aseptic conditions and various cytomorphological patterns were analysed according to the IAC Yokohama system for reporting breast fine needle aspirations. Result: Of the 417 cases included in the study, 328 cases were benign, 04 were atypical probably benign, 04 were suspicious for malignancy, 64 cases were malignant and 17 cases were inadequate for opinion. Fibroadenoma was found to be the most common breast lesion. Overall benign breast lesions are much more common than malignant lesions. Conclusion: FNAC is a useful tool to diagnose malignant lesions of the breast and help the surgeon in differentiating benign and malignant lesions. Early diagnosis aid in effective management of malignant lesions of the breast and thereby reducing the mortality in these patients.